Auctions with In-house Bids - Greve, T. (Penn State, 2023)
This paper studies the phenomenon of overlapping auction dates in the art market. Using hand-collected data from both Christie’s and Sotheby’s over the period January 2021 to December 2022, we find that the percentage of overlapping dates for the sale of art prints was between 50% and 91%. Using a two-period model, we show that it is best for an auction house to auction its items as the second house (i.e. in the second period), leading to an equilibrium where they align their auction dates to overlap.